PD-1/PD-L1 immune checkpoint inhibitors in metastatic triple-negative breast cancer: a systematic review and meta-analysis - Yu, Yinan; Jin, Xueying; Zhu, Xiaoling; Xu, Yan; Si, Wei; Zhao, Jianguo (Frontiers in Immunology, 2023)
Background PD-1/PD-L1 immune checkpoint inhibitors (ICIs) have been controversial in the treatment of metastatic triple negative breast cancer (mTNBC). We collected randomized controlled trials in accordance with the study and carried out meta-analysis to comprehensively evaluate the efficacy and safety of immune checkpoint inhibitors in mTNBC. Aim To systematically evaluate the efficacy and safety of PD-1/PD-L1 ICIs (hereinafter referred to as ICIs) in the treatment of mTNBC. Methods As of 2023.2.5, Medline, PubMed, Embase, Cochrane library database and Web of Science were searched to determine the study in accordance with the trial of ICIs in the treatment of mTNBC. The assessment endpoints included objective response rate (ORR), progression-free survival (PFS), overall survival (OS), and safety. Meta-analysis of the included studies was performed using Revman 5.4. Results A total of six trials with 3172 patients were included in this meta-analysis. The ORR of ICIs combined with chemotherapy was significantly improved compared with chemotherapy (HR=0.88, 95%CI: 0.81-0.94, I2 = 0%). For PFS, the experimental group were better than the control group in both intention-to-treat (ITT) population and PD-L1 positive population, showing statistical significance (ITT: HR=0.81, 95%CI: 0.74-0.89, P<0.05, I2 = 0%; PD-L1 positive: HR=0.72, 95%CI: 0.63-0.82, P<0.05, I2 = 18%); For OS, in the ITT population, no statistical difference was observed in either ICIs combined with chemotherapy(HR=0.92, 95%CI: 0.83-1.02, P=0.10)or immune monotherapy(HR=0.78, 95%CI: 0.44-1.36, P=0.37), in the PD-L1 positive population, ICIs group had better OS than chemotherapy group (HR=0.83, 95%CI: 0.74-0.93, P < 0.05); In safety, serious adverse event (SAE) was no statistically significant difference between the ICIs group and the chemotherapy group; however, the incidence of immune-related adverse event (irAE) was significantly higher in the ICIs group than in the chemotherapy group (HR=2.15, 95%CI: 1.45-3.19, P < 0.05). Conclusion ICIs combined with chemotherapy significantly improved the PFS of mTNBC, however, ICIs only improved the OS in PD-L1 positive people, and no statistical difference was observed in ITT population; while benefiting from ICIs, we found that irAE in ICIs group increased significantly, and its high rate of adverse events still needs to be taken seriously.